Developing integrated biology teaching material with Qur’an and Sunnah value - Siti Robiah; Ibnu Hajar; Sepita Ferazona; Desi Tri Lestari (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
This research aims to produce integrated biology teaching materials with the values of the Al-Qur’an and As-Sunnah that are valid and effective in improving cognitive, psychomotor, and strengthening students' faith and devotion. This development research (R&D) uses the ADDIE model which consists of five stages, i.e. analysis, design, development, implementation, and evaluation. The data collection techniques used were literature studies, observations, interviews, questionnaires, and tests. Data collection instruments used include interview sheets, validation sheets, questionnaire sheets, pre-test and post-test question sheets, observation sheets, and checklists. The teaching materials were validated by three validators (material experts, learning experts, Al-Qur’an/Hadist experts), and practitioners from several biology teachers from different schools. The data was analyzed quantitatively and qualitatively (triangulation). The research results showed that the teaching materials developed met the very valid category based on the assessment of material experts, learning experts, Al-Qur’an/Hadist experts, and practitioners. Moreover, the products received excellent responses from the students. The teaching materials could improve students’ cognitive and psychomotor and also increase students' values of faith and piety. Further action will be extended to schools, especially schools with Islamic nuances so that they can be used both as self-taught materials for students and as teaching materials for teachers to use in the learning process.